A Facile Synthesized Polymer Featuring B‐N Covalent Bond and Small Singlet‐Triplet Gap for High‐Performance Organic Solar Cells. Issue 16 (8th March 2021) - Pang, Shuting; Wang, Zhiqiang; Yuan, Xiyue; Pan, Langheng; Deng, Wanyuan; Tang, Haoran; Wu, Hongbin; Chen, Shanshan; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract: High‐efficiency organic solar cells (OSCs) largely rely on polymer donors. Herein, we report a new building block BNT and a relevant polymer PBNT‐BDD featuring B‐N covalent bond for application in OSCs. The BNT unit is synthesized in only 3 steps, leading to the facile synthesis of PBNT‐BDD. When blended with a nonfullerene acceptor Y6‐BO, PBNT‐BDD afforded a power conversion efficiency (PCE) of 16.1 % in an OSC, comparable to the benzo[1, 2‐b:4, 5‐b′]dithiophene (BDT)‐based counterpart. The nonradiative recombination energy loss of 0.19 eV was afforded by PBNT‐BDD. PBNT‐BDD also exhibited weak crystallinity and appropriate miscibility with Y6‐BO, benefitting of morphological stability. The singlet–triplet gap (Δ E ST ) of PBNT‐BDD is as low as 0.15 eV, which is much lower than those of common organic semiconductors (≥0.6 eV). As a result, the triplet state of PBNT‐BDD is higher than the charge transfer (CT) state, which would suppress the recombination via triplet state effectively. Abstract : An easily synthesized building block BNT and a relevant polymer PBNT‐BDD featuring B‐N covalent bond were synthesized for application in solar cells. The polymer offered a power conversion efficiency of 16.1 %, a nonradiative recombination energy loss of 0.19 eV, and a singlet‐triplet gap as low as 0.15 eV, demonstrating the promising prospect of B‐N‐containing materials in organic photovoltaics.